2012
DOI: 10.1038/nrneurol.2012.54
|View full text |Cite
|
Sign up to set email alerts
|

Pains in Parkinson disease—many syndromes under one umbrella

Abstract: Pain is a nonmotor symptom that substantially affects the quality of life of at least one-third of patients with Parkinson disease (PD). Interestingly, patients with PD frequently report different types of pain, and a successful approach to distinguish between these pains is required so that effective treatment strategies can be established. Differences between these pains are attributable to varying peripheral pain mechanisms, the role of motor symptoms in causing or amplifying pain, and the role of PD pathop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
178
0
21

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 209 publications
(221 citation statements)
references
References 125 publications
9
178
0
21
Order By: Relevance
“…This lack of studies could be explained by several epidemiological factors; for instance, FTD is relatively more prevalent in a younger population, whereas pain is more prevalent in the older population [4]. A specific reason for the lack of studies in DLB could be that these patients may be studied within trials assessing pain in PD, as Lewy body neuropathology is a key feature of PD and prevalence of pain in PD is estimated to be between 40 and 60% [34,35]. Furthermore, we found that the methods of pain assessment varied widely, and many of the used instruments were not specifically designed for the population, for example the EQ-5D, which is an instrument to measure quality of life and only incorporates one pain item.…”
Section: Discussionmentioning
confidence: 99%
“…This lack of studies could be explained by several epidemiological factors; for instance, FTD is relatively more prevalent in a younger population, whereas pain is more prevalent in the older population [4]. A specific reason for the lack of studies in DLB could be that these patients may be studied within trials assessing pain in PD, as Lewy body neuropathology is a key feature of PD and prevalence of pain in PD is estimated to be between 40 and 60% [34,35]. Furthermore, we found that the methods of pain assessment varied widely, and many of the used instruments were not specifically designed for the population, for example the EQ-5D, which is an instrument to measure quality of life and only incorporates one pain item.…”
Section: Discussionmentioning
confidence: 99%
“…PD patients have two different types of pain: nociceptive and neuropathic. Nociceptive pain is extremely frequent (40-90%) 27 and is typically musculoskeletal and visceral. Musculoskeletal pain is in general caused by abnormal posture, rigidity and akinesia causing motor fluctuations.…”
Section: Discussionmentioning
confidence: 99%
“…Pain has been more deeply studied in recent years as a PD symptom which substantially affects QL of at least one third of patients 11 . Considering our results, mean age of studied population and presence of pain, there has been no correlation, similarly to literature reports [12][13][14] .…”
Section: Discussionmentioning
confidence: 99%
“…Despite its prevalence in Lewy Body patients [46,47] and debilitating impact on quality of life, gastric immotility is rarely a focus of treatment for patients with PD and NCDLB [4,34,36,39,[53][54][55][56]. When PD and NCDLB constipation is addressed, primary care physicians typically recommend conventional (often overthe-counter) treatments, despite data demonstrating that such treatments are ineffective with this population [54].…”
Section: Symptom Treatment Of Cholinergic Lewy Pathology In the Ensmentioning
confidence: 99%
“…Escalating gastric immotility in PD and NCDLB can interfere with mobility, sleep, cognition, and mood, increasing the cost of care, and potentially debilitating and/or dramatically reducing the quality of life for patients. [4,34,36,[53][54][55][56] …”
mentioning
confidence: 99%